ANALISIS KEMANDIRIAN DAN KEMAMPUAN KEUANGAN DALAM MENDUKUNG OTONOMI DAERAH DI KABUPATEN BONE BOLANGO - Zubaidah Rahman; Pratiwi Laere (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This study aims to determine the Independence and Financial Capability of Regional Autonomy in Bone Bolango Regency. The object of research at the BKPD Office, Bone Bolango Regency. The ratio analysis method used is the Regional Financial Independence Ratio and Regional Financial Capability Ratio. The results of the analysis that have been carried out are that (2) the financial independence of Bone Bolango Regency based on the ratio of regional financial independence is very low to regional autonomy, (2) the financial capacity of Bone Bolango Regency based on the ratio of regional financial capacity is very low on regional autonomy.